Analisis Pelanggaran Etika Profesi Akuntan dalam Kasus Manipulasi Laporan Keuangan PT Wanaartha Life - Kevin Diaz Suith; Muhammad Ilham Kamal; Rehan Canta Yuda; Yanuar Ramadhan (Universitas Nusantara PGRI Kediri, 2026)
This study aims to examine violations of the accountant professional code of ethics in the financial scandal involving PT Asuransi Jiwa Adisarana Wanaartha (Wanaartha Life), which resulted in significant losses for thousands of policyholders. The scandal involved manipulated financial statements, a lack of transparency in investment fund management, and failures by external auditors to carry out their professional responsibilities. The research employs a descriptive approach through a literature study that draws upon secondary data from academic publications, official news sources, and documents containing OJK sanctions and investigative audit findings. The analysis reveals that several fundamental principles of the accounting profession’s code of ethics integrity, objectivity, professional competence and due care, confidentiality, and professional behavior were breached by both company management and the auditors involved. These violations are further supported by formal sanctions imposed on the public accountants and accounting firms proven to have participated in the improper financial reporting practices. Moreover, the study highlights the critical role of whistleblowing and investigative auditing as mitigation mechanisms for detecting fraud in financial reporting. The findings emphasize that non-compliance with professional ethics in accounting practices can generate broad impacts, including diminished public trust, disruption of financial sector stability, and weakened consumer protection. This study is expected to contribute as a reference for auditors, accountants, regulators, and academics in strengthening the implementation of professional ethics and corporate governance within the financial sector.